Efficacy of traditional Chinese exercise for sarcopenia: A systematic review and meta-analysis of randomized controlled trials - Niu, Kun; Liu, Ying-Lian; Yang, Fan; Wang, Yong; Zhou, Xia-Zhi; Qu, Qing (Frontiers in Neuroscience, 2022)
Objective To conduct a systematic review and meta-analysis to evaluate the effectiveness of Traditional Chinese Exercise (TCE) for sarcopenia. Methods A literature search was conducted in eight online databases from inception until September 2022. Based on the Cochrane risk of bias tool, randomized controlled trials (RCTs) with RoB score ≥ 4 were included for further analyses. The primary outcome was muscle strength and physical function, and the secondary outcomes were adverse events. Data collection and analyses were conducted by RevMan 5.4 Software. GRADE system was used to evaluate the certainty of evidence. Results A total of 13 eligible RCTs with 718 subjects were identified and included in this study. Among them, 10 RCTs involved Yijinjing; 2 involved Tai Chi; and 1 involved Baduanjin. Meta-analyses showed that TCE had better clinical effects than control measures in the chair stand test (P < 0.00001, I2 = 38%; Certainty of evidence: Moderate), squatting-to-standing test (P < 0.00001, I2 = 0%; Certainty of evidence: Moderate), 6-m gait speed (P < 0.00001, I2 = 13%; Certainty of evidence: Moderate), Time Up and Go Test (P = 0.03, I2 = 81%; Certainty of evidence: Low), peak torque of the extensors (P = 0.03, I2 = 0%; Certainty of evidence: Moderate), total work of the extensors (P = 0.03, I2 = 35%; Certainty of evidence: Moderate), peak torque of the flexors (P = 0.03, I2 = 47%; Certainty of evidence: Low), total work of the flexors (P = 0.02, I2 = 42%; Certainty of evidence: Low), the average power of the flexors (P = 0.03, I2 = 30%; Certainty of evidence: Moderate), and balance function (P < 0.00001, I2 = 53%; Certainty of evidence: Low). In additional, no adverse events were reported in participants who receive TCE. Conclusion The findings of the present systematic review, at least to a certain extent, provided supporting evidence for the routine use of TCE for sarcopenia.